PENGEMBANGAN DESAIN MESIN CNC ROUTER SEBAGAI MEDIA PEMBELAJARAN DI JURUSAN TEKNIK MESIN - Abdul Salam; Syaharuddin Rasyid; Muhammad Nisam Sumule , (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
Th e objectives to be achieved in this research on the design of the CNC Router machine are to support size precision in the manufacture ofengraving/engraving products on acrylic, wood, and multi-triple workpieces and to know the estimated cost of manufacturing CNC Router machines.The stages of research carried out are making, designing, testing, and analyzing test data. The research method is carried out by selecting tools andmaterials, work procedures and steps, assembly stage, and testing process. The data collection method was carried out using different materials,namely acrylic and multiplex and measuring the level of precision in the manufacture of engraving/engraving products on acrylic plastic andmultiplex wood workpieces. The conclusion of this research has been that a CNC Router machine has been designed according to the Arduino control system so that the machine can be operated according to its function. In this case, the CNC Router machine has been able to executeworkpieces made of acrylic and multiplex with various patterns using the NC program command. with the test results it can be seen that the X, Y,and Z axes are in accordance with the actual movement of the X, Y, and Z axis machines